Intravenous immunoglobulin in necrotizing fasciitis – A case report and review of recent literature. Issue 3 (September 2015) - Koch, C.; Hecker, A.; Grau, V.; Padberg, W.; Wolff, M.; Henrich, M.
Abstract: Introduction: Necrotizing fasciitis (NF) is an inflammatory disease of the soft tissue, which causes local tissue destruction and can lead to lethal septic shock. The therapy consists of early surgical treatment of the septic focus and an accompanying broad spectrum antibiotic therapy. Recent literature considers the additional use of immunoglobulin therapy in severe soft skin and tissue infections. Presentation of case: In this report, we describe the case of a 33-year-old male patient treated at a university hospital intensive care unit because of an NF of his left leg. The patient rapidly developed a complicated septic disease after a minor superficial trauma. Despite intense microbiological diagnosis, no causative pathogens were identified. After non-responding to established broad anti-infective treatment, the patient received intravenous immunoglobulin, that rapidly improved his clinical condition. Discussion: NF represents a disease processes, which is characterized by fulminant, widespread necrosis of soft tissue, systemic toxicity, and high mortality (>30%). Beside the surgical debridement and broad spectrum antibiotic therapy IVIg therapy might be an additional option in the treatment of NF. But the current literature supporting the use of IVIG in NF is largely based on retrospective or case-controlled studies, and only small randomized trials. Conclusion: The demonstrated case suggests that IVIg treatment of patients with NF can be considered in case of hemodynamic unstable, critically ill patients. Although randomized controlled trials are missing, some patients might benefit from diminishing hyperinflammation by immunoglobins. Highlights: Necrotizing fasciitis (NF) is an inflammatory disease, which causes local tissue destruction up to lethal septic shock. We describe the case of a 33-year-old male patient representing an NF of his left leg. After non-responding to established broad anti-infective treatment, the patient received immunoglobulin (IVIg). The presented case suggests that IVIg treatment of patients with NF might be considered in case of critically ill patients.